APPLICABILITY AND EFFECTIVENESS IN THE METHODOLOGICAL ACTIONS OF THE THEMATIC AXES: IN THE NORMATIVE INSTRUCTION SEE Nº 08/2020 OF EJA CAMPO - Aparecida Dantas Bezerra, Maria (Revista Gênero e Interdisciplinaridade, 2023)
This article reflects on the methodological actions of the thematic axes of EJA Campo and Special Education, with the intervention of Normative Instruction SEE Nº 08/2020, entering into the inclusion of both modalities in the educational context in the regular room of EJA Campo in rural communities . In this sense, the research was approached in a case study, whose theoretical reference survey was carried out through bibliographical and documental research in the methodological actions of the EJA Field and Inclusion of Special Education, in the intervention of the Normative Instruction SEE Nº 08/2020 and Brazilian Inclusion Law 06/07/2015. For that, we developed a qualitative research analysis whose preliminary results of the formative practices are included in the articulating and thematic axes of the curricular components where they are developed according to the cultural practice of each student using the Pedagogy of Alternation.